Efek Edukasi Tatap Muka versus Media Dalam Inisiasi Insulin Terhadap Pengetahuan dan Kualitas Hidup Pasien DMT2 di Masa Pandemi Covid-19 - Firdausa, Sarah; Irwansyah, Irwansyah; Ariani, Reva; Nadya, Ahsana (LITBANG RSUDZA, 2021)
The Covid-19 pandemic is a threat for diabetic patients as they are prone to be worse once they got infected with the Sars-Cov-2 virus, especially in uncontrolled diabetes patients. Insulin is one of the modalities of diabetes treatment, especially in patients who have not reached the therapeutic target. Initiation of insulin is still often hampered due to lack of good education to patients. Providing face-to-face education during the Covid-19 pandemic poses a greater risk of virus transmission, therefore insulin initiation education needs to be carried out with effective communication methods. This study aims to implement interpersonal education in initiating insulin in type 2 diabetes patients using technology such as videos and educational booklets at the Hospital Dr. Zainoel Abidin, Banda Aceh. This study uses a quasi-experimental design with a pre and post-test approach. The sample collection technique was total sampling, namely all diabetic patients who received insulin initiation in July - October 2021. There were 38 respondents divided into 17 respondents for the control group and 21 respondents for the intervention group. Questionnaire data was collected before and before the intervention. Knowledge data is presented descriptively, data and quality of life before and before intervention were analyzed by t-test. The results showed that the knowledge of the respondents before and before education was good, there was no difference in knowledge before and before the intervention, both in the oral group, and in the video group. After the intervention, the mean quality of life scores improved significantly in both the oral and media groups. Conclusion: There is no significant difference between face-to-face education (oral) and education using media (videos and booklets). The effect of education orally or through the media on the knowledge and quality of life of diabetic patients is the same.